Bidirectional nuclear polarization through electric dipole spin resonance enabled by spin-orbit interaction in a single hole planar quantum dot device - Sergei Studenikin; Jordan Ducatel; Olivia Ellis; Marek Korkusinski; Alex Bogan; Piotr Zawadzki; D. Guy Austing; Andrew Sachrajda (npj Quantum Information)
Abstract Spin exchange between confined holes and nuclei has been demonstrated for zero-dimensional quantum dots by optical techniques but has not been observed for gated planar structures. Here, enabled by strong spin-orbit interaction, and under microwave (MW) illumination, we report hyperfine interaction and dynamic polarization of the nuclei with confined heavy-holes in a GaAs/AlGaAs double quantum dot device. Distinct signatures of the resultant hyperfine field on the electron dipole spin resonance (EDSR) signal include: hysteresis on sweeping the magnetic (B-) field up and down with characteristics that are strongly dependent on both MW power and B-field sweep rate; free bidirectional dragging of the EDSR condition; stable locking on resonance on a timescale of hours; slow temporal change as the hyperfine field decays (T1 nuclear decay time ~ 100 s); and oscillations in time commensurate with Larmor precession of the 75As nuclei. We attain pumped nuclear (Overhauser) fields ~ 25 mT (~20% nuclear polarization).